OP0236 Different Scoring Methods of FDG PET/CT in Giant Cell Arteritis: Need for Standardization. (9th June 2015) - Brouwer, E.; Arends, S.; Stellingwerf, M.; Lensen, K.-J.; Rutgers, A.; van der Geest, N.; Glaudemans, A.; Slart, R.
Abstract : Background: Giant cell arteritis (GCA) is the most frequent form of vasculitis in persons older than 50 years. Cranial and systemic large vessels can be involved. [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography (PET)/ computed tomography (CT) is increasingly used to diagnose inflammation of the large arteries in GCA. Unfortunately, no consensus exists on the preferred scoring method. Objectives: In the present study, we aim to define the optimal scoring method for GCA for FDG PET/CT, using temporal artery biopsy and clinical diagnosis as the reference method. Methods: FDG PET/CT scans of GCA patients (glucocorticoid-naïve n=12, on glucocorticoid treatment n=6) and 3 control groups (inflammatory n=18, atherosclerotic n=19, normal controls n=16) were evaluated. We compared two qualitative visual methods (i.e. (1a) first impression and (1b) vascular uptake versus liver uptake) and four semi-quantitative methods ((2a) SUVmax aorta, (2b) SUVmax aorta-to-liver ratio, (2c) SUVmax aorta-to-superior-caval-vein ratio and (2d) SUVmax aorta-to-inferior-caval-vein ratio). FDG uptake pattern (diffuse or focal) and presence of arterial calcifications were also scored Results: Accuracy of the visual method vascular versus liver uptake was highest when using the cut-off point "vascular uptake higher than liver uptake" (sensitivity 83%, specificity 91%). Sensitivity increased to 92% when patients on glucocorticoids were excluded from the analysis. Regarding the semi-quantitative methods, the SUVmax aorta-to-liver cut-off ratio had the highest accuracy. The optimal cut-off point was 1.03, with sensitivity being 69% and specificity 92%. Sensitivity increased to 90% when excluding patients on glucocorticoids. The number of vascular segments with diffuse uptake pattern was significantly higher in GCA patients without glucocorticoid use compared with all control patient groups. CRP was not significantly different between positive and negative FDG PET scans in the GCA group. Conclusions: Visual vascular uptake higher than liver uptake resulted in the highest accuracy for the detection of GCA, especially in combination with a diffuse uptake pattern. An aorta-to-liver SUVmax ratio higher than 1.03 had the highest accuracy as semi-quantitative method. The accuracy increased when excluding patients using glucocorticoids from the analyses. Acknowledgements: We received a special grant from the NC Smit/Dutch Arthritis Association for our GCA cohort. Disclosure of Interest: None declared